The Levels of Wnt5a and Its Receptors Frizzled5 and Frizzled2 as Immunohistochemical Biomarkers of Severity of Psoriasis - Ning X (Dove Medical Press, 2021)
Xiaoying Ning, Dingwei Zhang, Yuan Wang, Jia Huo, Ying Huang, Ying Guo, Zhengxiao Li, Yanfei Zhang Department of Dermatology, The Second Affiliated Hospital of Xi’an Jiaotong University, Xian, Shaanxi Province, People’s Republic of ChinaCorrespondence: Zhengxiao Li; Yanfei ZhangDepartment of Dermatology, The Second Affiliated Hospital of Xi’an Jiaotong University, 157 Xi Wu Road, Xian, Shaanxi Province, 710004, People’s Republic of ChinaTel/Fax +86-29-87679301Email lizhengxiao1979@163.com; zhangyanfei723@163.comPurpose: Psoriasis is a systemic, chronic and inflammatory condition. The exact pathogenesis is unclear. The abnormal expression of Wnt5a pathway in psoriasis vulgaris has been confirmed. Whether it is related to the severity of psoriasis is unclear.Methods: Thirty-eight skin lesions from psoriasis vulgaris patients and 22 healthy adult skin tissues were taken. The semi-quantitative immunohistochemistry score of Wnt5a, Frizzled5 and Frizzled2 was evaluated under a microscope by two independent dermatologists. Psoriasis area and severity index (PASI) score system was used to evaluate the disease severity.Results: The average PASI score of the patients was 16.25 ± 7.8, and the average duration of disease was 19.6 ± 10.4 months. Wnt5a, Frizzled5 and Frizzled2 were highly expressed in psoriasis lesions. The semi-quantitative immunohistochemistry scores of Wnt5a, Frizzled5 and Frizzled2 were positively correlated with PASI scores (r = 0.71, r = 0.46, r = 0.65, respectively, all P-value < 0.01), but not correlated with duration of disease (r = 0.11, r = 0.17, r = 0.29, respectively, all P-value > 0.05). There were significant positive correlations between Wnt5a and Frizzled5 (r = 0.57, P-value < 0.01), as well as Wnt5a and Frizzled2 (r = 0.59, P-value < 0.01).Conclusion: Wnt5a and its receptors play an important role in pathogenesis of psoriasis vulgaris and are positively correlated with the severity of psoriasis, and may be one of the immunohistochemical predictors of the severity of the disease.Keywords: psoriasis vulgaris, Wnt5a, PASI, Frizzled5, Frizzled2